2021
DOI: 10.1002/hbm.25537
|View full text |Cite
|
Sign up to set email alerts
|

Functional impairment‐based segmentation of anterior cingulate cortex in depression and its relationship with treatment effects

Abstract: In major depressive disorder (MDD), the anterior cingulate cortex (ACC) is widely related to depression impairment and antidepressant treatment response. The multiplicity of ACC subdivisions calls for a fine-grained investigation of their functional impairment and recovery profiles. We recorded resting state fMRI signals from 59 MDD patients twice before and after 12-week antidepressant treatment, as well as 59 healthy controls (HCs). With functional connectivity (FC) between each ACC voxel and four regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…One large study found that higher connectivity between the pregenual ACC and the cerebellum, PCC, and right occipital cortex and lower connectivity to the dlPFC, anterior medial PFC, right subgenual ACC, right caudate nucleus, right STG, left insula, and right extrastriate cortex differentiates early remitters from late remitters ( van der Wijk et al, 2022 ). Another study reported deficits in subgenual ACC to dlPFC and dorsal ACC to right amygdala connectivity between depressed participants and healthy controls that normalized with treatment, but did not directly relate this to remission or response status ( Zhang, 2021 , Zhang, 2021 ). Finally, examination of dynamic FC in a large first-episode study reported that the pregenual ACC maintains a more stable connectivity pattern in responders than non-responders ( Tian, 2019 ).…”
Section: Functional Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One large study found that higher connectivity between the pregenual ACC and the cerebellum, PCC, and right occipital cortex and lower connectivity to the dlPFC, anterior medial PFC, right subgenual ACC, right caudate nucleus, right STG, left insula, and right extrastriate cortex differentiates early remitters from late remitters ( van der Wijk et al, 2022 ). Another study reported deficits in subgenual ACC to dlPFC and dorsal ACC to right amygdala connectivity between depressed participants and healthy controls that normalized with treatment, but did not directly relate this to remission or response status ( Zhang, 2021 , Zhang, 2021 ). Finally, examination of dynamic FC in a large first-episode study reported that the pregenual ACC maintains a more stable connectivity pattern in responders than non-responders ( Tian, 2019 ).…”
Section: Functional Predictorsmentioning
confidence: 99%
“…A study in LLD reported that whole-brain eigenvector centrality, a measure of a region’s influence/degree of connectivity in a given network, was positively associated with remission in the left inferior frontal gyrus and negatively associated in the right parahippocampus, right fusiform gyrus, and left caudate nucleus ( Karim, 2018 ). It has also been reported that degree centrality, a measure of total FC strength, increases in the hippocampus and decreases in the dmPFC over the course of treatment are associated with symptomatic improvement ( Wang, 2015 ) and that global characteristic path length, a measure of network efficiency, is negatively associated with reduction in depressive symptoms (large study) ( Zhang, 2021 , Zhang, 2021 ). Finally, a study investigating longitudinal changes in DMN subsystems reported that average connectivity within the core DMN network increased with treatment (normalized relative to healthy controls) without regard to treatment outcome ( Cui et al, 2021 ).…”
Section: Functional Predictorsmentioning
confidence: 99%
“…Increasing neuroimaging evidences also showed ACC played a vital role in MDD. For example, a study from China found the functional connectivity between the Distal ACC and left DLPFC was impaired, while, it got normalized after 12-week antidepressant treatment [ 43 ]. Jin et al found aberrant structural connectivity between the rostral ACC and amygdala prospectively predates first onset of MDD [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have identified the ACC as an important region associated with the response to antidepressant treatment. For example, a resting MRI study observed that 12 weeks of antidepressant treatment normalized functional connectivity between the Distal ACC and the left dorsolateral prefrontal cortex, contributing to the prediction of clinical outcomes, suggesting that the damaged ACC can be partially restored after antidepressant treatment ( Zhang et al, 2021 ). Even 8 weeks of antidepressant treatment induced a faster rate of symptoms improvement, which was closely associated with a larger gray matter volume in the ACC ( Chen et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%